The INFORMATION SYSTEM WEB-BASED ACCEPTANCE OF NEW STUDENTS (CASE STUDY: SMK N KARTOHARJO MAGETAN): web-based acceptance of new students - Fatkhur Rokhman (LPPM Universitas Merdeka Madiun, 2023)
The development of information technology today cannot be separated from all human activities, information technology also affects the field of education. In this case, the Admission of New Students at SMKN Kartoharjo Magetan still applies a manual registration system, namely by coming directly to the school to get a registration form from the school. To solve the problem above, an application was made entitled